Komunitas Lima Gunung: Concept of Art Communitas on Five Slopes Mountain of Central Java, Indonesia - Brian Trinanda Kusuma Adi; Samsul Ma’arif (ASSOCIATION FOR SCIENTIFIC COMPUTING ELECTRICAL AND ENGINEERING (ASCEE), 2020)
Komunitas Lima Gunung (KLG, the five-mountain community) was founded in 2002 by Sutanto Mendut—a well-known budayawan (cultural practitioner). KLG refers to communities living in areas of the five mountains of Magelang, Central Java that together join into one single organization, the KLG. Those mountains are the Mount Sumbing, Merbabu, Andong, Merapi, and Menoreh. Sutanto Mendut, the president of KLG, builds the community with the characteristics of what Victor Turner may call communitas, which is traditionally inherited in the calendrical ritual performances of KLG in which those groups of people continually re-articulate and re-contextualize their worldviews and social norms and orders. This research examines those ideas of communitas as forged in the KLG. This research was conducted through fieldwork: participant observation and unstructured interviews. Data were collected by participating in and documenting several activities (performances). “Meanings” of those performances were gathered through a series of unstructured interviews with practitioners that included Sutanto Mendut himself, leaders of the communities, and many members of the KLG. This research is indebted to theories of performance studies to analyze those collected data. The results of this study indicate that first, society emerges through ritual performances that create moments of liminality. This moment is the result of the re-articulation of the anti-norms/social order structure/structure. Second, Sutanto Mendut, through the Land Oath, re-articulated the sense of togetherness of KLG to become the Five Mountains Festival (FLG). Third, KLG is the strength of the community; members learn about freedom and are not dependent on established social structures. They are free to feel the moment of togetherness.